Quantitative Analysis of National Medicine Strategic Policies towards Internationalization of Traditional Chinese Medicine - Wang, Yinhan; Guo, Yan; Liu, Haolong; Liu, Cai (Transactions on Social Science, Education and Humanities Research, 2023)
Objectives To evaluate national strategic policy documents for internationalization of Traditional Chinese medicine in terms of the perspective of policy tools and their strengths and weaknesses, and to provide benchmark information for the policy development for internationalization of Traditional Chinese medicine. Methods Based on the content analysis method, we constructed a two-dimensional analysis framework of policy tools and code classification of Traditional Chinese medicine towards the international market, and classified and statistically analyzed the content of the text. Results A total of 198 codes were categorized in the content analysis unit with 18 policy texts. The x-dimension results showed that supply-based policy tools were used most frequently (66.2%), followed by environmental policy tools (20.7%), and demand-based policy tools were least used (13.1%); and the y-dimension results showed that the supply-based policy tools and demand-based supply were more applicable to scientific research and innovation, while Traditional Chinese medicine was more applicable to environmental policy tools. Conclusion: There is an overall imbalance in the policy tools, and the government needs to formulate targeted policy documents to optimize and adjust the system of TCM to the international arena.